Implementasi Algoritma Vernam Cipher Untuk Keamanan Data Nilai Siswa Studi Kasus SMK Swasta Rahmat Islamiyah Medan - Raihan Arya Dhani; Leni Marlina; Juliandri (Bahasa Indonesia, 2026)
Student score data at SMK Swasta Rahmat Islamiyah Medan must be protected to prevent unauthorized access, modification, or data loss. To ensure confidentiality and data integrity, this research implements the Vernam Cipher encryption algorithm, which uses a one-time pad key and XOR operations to secure data. The algorithm provides strong protection when the key is used only once and kept confidential. By applying Vernam Cipher to the student score data process, all stored or transmitted information becomes unreadable without the correct key. This method helps reduce the risk of data leakage and manipulation. The results show that Vernam Cipher is effective in enhancing the security of student score data, ensuring a fair and reliable assessment process.